Thio-Michael–Aldol–Cyclization Cascade of N-Enoyl Thiazolidinethiones with Aliphatic Aldehydes and Cyclic Ketones - Rivas, Veronica M.; Munive, Laura; Olivo, Horacio F. (Synlett, 2014)
A thio-Michael–aldol–cyclization cascade reaction of N-enoyl thiazolidinethiones with aliphatic aldehydes and cyclic ketones was promoted by Ti(IV) chloride to deliver highly complex tricyclic adducts possessing a carbon atom tetrasubstituted with heteroatoms and up to four stereogenic centers in good to very good yields.
Keywords: asymmetric synthesis; cascade reaction; chiral auxiliaries; thiazolidinethiones; Ti(IV) chloride